Detection of Organic Carbon in Mars‐Analog Paleosols With Thermal and Evolved Gas Analysis. Issue 8 (5th August 2022) - Broz, Adrian P.; Clark, Joanna; Sutter, Brad; Ming, Doug W.; Horgan, Briony; Archer, Paul Douglas; Silva, Lucas C. R.
Abstract: Ancient, buried soils, or paleosols, may have been preserved in the geological record on Mars, and are considered high‐priority targets for biosignature investigation. Studies of paleosols on Earth that are similar in composition to putative martian paleosols can provide a reference frame for constraining their organic preservation potential on Mars. However, terrestrial paleosols typically preserve only trace amounts of organic carbon, and determining what carbon is original is complicated by diagenesis and additions of modern carbon. The objectives of this study were (a) to determine whether organic carbon in Mars‐analog paleosols can be detected with thermal and evolved gas analysis, and (b) constrain the age of organic carbon using radiocarbon ( 14 C) dating. Oligocene (33 Ma) paleosols from Oregon were examined with an instrument similar to the Sample Analysis at Mars Evolved Gas Analysis instrument onboard the Mars Science Laboratory Curiosity rover. Trace amounts of organic carbon and fragments of organic molecules were observed in all samples. Total organic carbon (TOC) ranged from 0.002 to 0.032 ± 0.006 wt. %. The near‐surface horizons of paleosols had significantly higher TOC relative to subsurface layers. Radiocarbon dating of four samples revealed an organic carbon age of ∼6, 200–14, 500 years before present and a fraction modern ranging from 0.16 to 0.46. Modeled abundances of modern carbon in bulk samples ranged from 0.41%–3.1% ± 0.11%, which were consistent with additions of small amounts of modern organic carbon. This work demonstrates that martian paleosols are a potential high priority location for in‐situ biosignature investigation. Plain Language Summary: Ancient, buried soils, or paleosols, may have been preserved in the geological record on Mars. On Earth, paleosols that are billions of years old contain signs of ancient life (biosignatures) and therefore paleosols on Mars are considered high‐priority locations for biosignature investigation. One way to determine the biosignature preservation potential of possible martian paleosols is to examine organic carbon preservation in paleosols from Earth that resemble martian paleosols. The objectives of this work were to determine if carbon in Mars‐analog paleosols can be detected by an instrument configured to operate like the Sample Analysis at Mars Evolved Gas Analyzer onboard Curiosity rover, and to use radiocarbon dating to determine if samples contain modern carbon. Trace amounts of organic carbon and fragments of organic molecules were observed. Like modern soils, the near‐surface horizons of all paleosols had significantly higher amounts of carbon relative to subsurface layers. Radiocarbon dating revealed an organic carbon age of ∼6, 200–14, 500 years before present. Application of an isotopic mixing model suggested these dates could be explained by slight additions of modern carbon to ancient samples. These results demonstrate that putative martian paleosols are a potential high priority location for in‐situ biosignature investigation. Key Points: Trace amounts of organic carbon (OC) in Mars‐analog paleosols were detected with thermal and evolved gas analysis The near‐surface horizons of 33‐million‐year‐old paleosols had significantly higher OC content relative to deeper layers Radiocarbon dates of approximately 6–14 thousand years were consistent with small amounts of modern carbon in paleosol samples